PENGARUH PMK NO.91/PMK.03/2015 DAN PMK NO. 197/PMK.03/2015 TERHADAP PENERIMAAN PAJAK DI KPP PRATAMA JAKARTA KEBON JERUK SATU - LIVYA LIVYA; IDA BAGUS NYOMAN SUKADANA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to know the procedures for filling a petition for reduction and elimination of administrative sanctions based on PMK No.91/PMK.03/2015 and PMK No.197/PMK.03/2015 and to know the amount of petition that was granted as well as the influence of PMK No.91/PMK.03/2015 and PMK No.197/PMK.03/2015 against tax receipt in KPP Pratama Jakarta Kebon Jeruk Satu. The collecting of data using secondary data that has been processed at the PDI. Use data analysis tools the analysis descriptive. The influence of the acceptance of PMK No.91/PMK.03/2015 and PMK No.197/PMK.03/2015 not any real effect on tax revenues in the KPP Pratama Jakarta Kebon Jeruk Satu.